EFFECTIVENESS OF PROGRAMS IN SEXUAL AND REPRODUCTIVE EDUCATION IN ADOLESCENTS - Jacinto Cardenas, Renata; Ruiz Paloalto , Ma. Laura (Horizonte Sanitario, 2021)
Introduction: Adolescence is a crucial stage in the development of human sexuality. Adolescents need answers to their ignorance and their doubts on the subject. Sexuality is an issue that is not addressed regularly in the family or school environment. Healthy sexuality is framed in the context of health promotion, responding to the students’ needs regarding knowledge, positive and demystified sexuality, preserving the rights of people, without discrimination or violence. Objective: to identify and analyze scientific publications on sexual health and reproductive from the perspective of the educational group. Method: integrative review of the scientific literature in the national database of the Virtual Health Library during 2015-2019, based on articles that focused on the application of educational programs on sexual and reproductive health in adolescents. Results: The research findings confirm the importance of educational programs in reproductive health as a basis for improving the knowledge of adolescents and giving them tools to feel prepared, make better decisions and face important situations related to their sexual and reproductive health. Of the articles identified with inclusion and exclusion criteria, 8 were selected. Conclusion: the educational program allows increasing the knowledge of adolescents on issues of sexual and reproductive health; therefore, its effectiveness is corroborated.